Personal and Organizational Excellence through Servant Leadership: Learning to Serve, Serving to Lead, Leading to Transform - Sendjaya, Sen (Springer, 2015)
This book provides an evidence-based actionable framework and measure of servant leadership to help management practitioners build effective and ethical workplaces. It explains the reasons why the best workplaces such as Starbucks, Southwest Airlines, Ritz-Carlton and ServiceMaster apply servant leadership. Servant leadership is an intellectually compelling and emotionally satisfying theory of leadership with relevance and application to the workplace settings. Based on multiple rigorous studies in the Western and Eastern contexts, the book outlines the six dimensions of servant leadership and the impacts they have on key outcomes such as citizenship behaviors, job satisfaction, team creativity and innovation, and organizational performance. The book outlines a measurement instrument that can be used for leadership assessment, selection and training purposes and to develop strategies to leverage the six behavioral dimensions of servant leadership at the personal, team and organizational level.